Absorb Bioresorbable Vascular Scaffold in Complex Coronary Bifurcation Interventions: Insights From an In Vivo Multimodality Imaging Study. (August 2016) - Bennett, Johan; Vanhaverbeke, Maarten; Vanden Driessche, Nina; Adriaenssens, Tom; Hiltrop, Nick; Desmet, Walter; Sinnaeve, Peter; Dubois, Christophe
Abstract : Background—: Although bioresorbable scaffolds offer potential advantages compared with metallic drug-eluting stents in the treatment of complex coronary bifurcation lesions, there are concerns that the polymeric scaffold integrity may be compromised. This in vivo study sought to provide insights about the feasibility of performing complex bifurcation stenting with Absorb bioresorbable vascular scaffolds (Abbott Vascular, Santa Clara, CA). Methods and Results—: Twenty New Zealand white rabbits underwent stenting of the nondiseased aortoiliac bifurcation with bioresorbable vascular scaffolds using provisional (PS, n=5), culotte (n=5), modified-T (n=5), or T-and protrusion (n=5) stenting techniques. Angiography, optical coherence tomography, and microcomputed tomography were performed. Angiographic results were excellent without evidence of dissection or side branch (SB) compromise. PS optimally opened the SB ostium without deforming the main vessel (MV) bioresorbable vascular scaffolds, avoiding malapposition, and revealing a single connector fracture in 1 of 5 cases on microcomputed tomography. Culotte stenting resulted in complete bifurcation coverage with extensive segments of double-layered struts and inappropriately apposed struts at the bifurcation level in 3 of 5 cases. On microcomputed tomography, there was MV and SB scaffold distortion at the bifurcation with single strut fractures in 4 of 5 and double fractures in 1 of 5. Modified-T and T-and protrusion resulted in complete bifurcation coverage and in minimal double-strut layers at the neocarina. On microcomputed tomography, no strut fractures were present after modified-T, whereas in 3 of 5 T-and protrusion procedures single strut fractures were noted. Conclusions—: Bifurcation stenting using bioresorbable vascular scaffolds is feasible with excellent angiographic results. PS with additional T-and protrusion whenever needed seems a reasonable approach. Whenever a 2-stent technique is planned, modified T-stenting appears the most promising. Abstract : Supplemental Digital Content is available in the text.